Assessment of a method for usability testing by determining usability of the online learning platform - Števančec, Darko (Mednarodno inovativno poslovanje, 2019)
Today many products are designed to be reasonably easy to use so, in addition to usefulness, product usability is of great importance. Usability means simply using or simply learning to use a tool or device. In software engineering, usability is the degree to which certain users can effectively use software to achieve their goals in thecontext of use. Usability assessment involves measurement methods, such as analyzing consumer needs and examining perceptions of product efficiency and product attractiveness. In human-computer interaction, studying usability means the analysis of attractiveness and clarity of an application which is designed to interact with a computer program or web site.
Keywords: e-learning; e-študij; method; učne metode; uporabnost; usability